The relevance of smaller municipalities and small-scale potential for infill development. A quantitative monitoring using the example of Germany - Schiller, Georg; Blum, Andreas; Oertel, Holger (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
The limitation of land use and the protection of soil is an important target set in European and national sustainability strategies. To this end, the use of brownfields, vacant and underutilised sites within existing settlement structures for urban development, frequently called infill development, is a primary strategy. This paper presents the results of a nationwide survey to generate reliable data on the potential for infill development in German cities and towns. In contrast to earlier studies, in particular infill development potential in small communities and small-scale potential, usually on vacant lots, are focused and discussed with regard to their relevance for land-saving settlement-policy making. The data generated allow to determine a reliable range of overall infill development potential per capita of at least 15 m2. Often underestimated, the survey also reveals, that more than a quarter of infill development potential is located in smaller communities below 5.000 inhabitants, which were not included in earlier surveys. With respect to lot sizes the results also show that small-scale potential on vacant lots makes up more than half of the overall potential. It is thus recommended that policy making towards sustainable land use put more emphasis on small-scale land uses and awareness rising in smaller communities which clearly tend to underestimate their infill potential.
Keywords: Infill development potential; Land use; Small cities; Brownfields; Vacant lots; Land saving settlement policy